2015
DOI: 10.1111/acfi.12136
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the global financial crisis on Islamic and conventional stocks and bonds

Abstract: This study explores the impact of the global financial crisis (GFC) on Islamic and conventional stock and bond indices in 11 Islamic and eight non-Islamic countries. We find that there are benefits of Islamic stocks during the GFC, particularly during the early stage of the crisis because Islamic institutions are prohibited from holding sub-prime mortgage securities and derivatives. The strongest benefits of Islamic stocks are in the UK and USA. We conclude that there are benefits of risk reduction and stabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(32 citation statements)
references
References 56 publications
(79 reference statements)
0
28
0
4
Order By: Relevance
“…In conclusion, previous research on the financial performance of Islamic indices is split between studies finding them to outperform during bear markets and underperform during bull markets (i.e., Al-Khazali et al, 2014, Akhtar andJahromi, 2015), while the earlier work of Hussein and Omran (2005) found the opposite and several large recent studies of multiple index providers found no significant performance difference (LOBE et al, 2012;ASHRAF, 2016). There also appears to be some evidence of a better performance in developed than in emerging markets but none of these studies controlled for backtesting bias inherent in the indices of several providers, which make historical data available for multiple years prior to the actual index launch (WALKSHÄUSL; LOBE, 2012a, 2012b).…”
Section: Empirical Evidence On Islamic Index Performancementioning
confidence: 85%
See 1 more Smart Citation
“…In conclusion, previous research on the financial performance of Islamic indices is split between studies finding them to outperform during bear markets and underperform during bull markets (i.e., Al-Khazali et al, 2014, Akhtar andJahromi, 2015), while the earlier work of Hussein and Omran (2005) found the opposite and several large recent studies of multiple index providers found no significant performance difference (LOBE et al, 2012;ASHRAF, 2016). There also appears to be some evidence of a better performance in developed than in emerging markets but none of these studies controlled for backtesting bias inherent in the indices of several providers, which make historical data available for multiple years prior to the actual index launch (WALKSHÄUSL; LOBE, 2012a, 2012b).…”
Section: Empirical Evidence On Islamic Index Performancementioning
confidence: 85%
“…Previous research on the financial performance of Islamic indices displays conflicting results. Some recent studies find them to outperform during bear markets and underperform during bull markets (e.g., Al-Khazali et al, 2014;AKHTAR;JAHROMI, 2015). In contrast, the earlier work of Hussein and Omran (2005) found the opposite and several recent studies of multiple index providers observed no significant performance difference (LOBE et al, 2012;ASHRAF, 2016).…”
Section: Introductionmentioning
confidence: 96%
“…This is perhaps due to Islamic stocks exclude many interest-based financial institution stocks which suffer from considerable decrease in their stock prices during the financial crises. Moreover, Islamic markets are prohibited from holding sub-prime mortgage securities and derivatives and hence Islamic stocks enjoy the benefits of risk reduction and stability during the global financial crisis (Akhtar & Jahromi 2017). Table 5 examines the impact of financial crises on the stock risk.…”
Section: Risk and Financial Crisesmentioning
confidence: 99%
“…In addition, Islamic markets are prohibited from holding sub-prime mortgage securities and derivatives. These characteristics result in Islamic stocks tend to be more stable and less risky compared to conventional stocks during market downturn and financial crises (Akhtar & Jahromi 2017;Dewandaru et al 2015). Taken together, the growing demand of Islamic equity investments, different stock characteristics and diverse business cycles motivate us to examine the link between business cycles, financial crises and the risk of Islamic and conventional stocks in the Malaysian setting.…”
Section: Introductionmentioning
confidence: 99%
“…For example, there were three changes of Prime Minister between 2010 and 2013; see Smales (2015) for more details. 9 In contrast to the capital structure literature, there are more studies conducted during the GFC period in other areas, such as audit committee ; financial risk management (Ganegoda and Evans, 2014); superannuation investment choices (Gerrans, 2012); individual financial risk tolerance (Gerrans et al, 2015); banking (Akhtar and Jahromi, 2015); corporate governance (Adams, 2012); bank risk taking behaviour (Hoang, Faff, and Haq, 2014); trade credit (Kestens, Cauwenberge, and Bauwhede, 2012), bank regulation (Levine, 2012); and accounting areas (Mala and Chand, 2012;Xu et al, 2013). Having said that, there are two recent studies slightly related to the financial crisis by examining capital structure issues through business cycles (Akhtar, 2012;Liu and Chen, 2012).…”
Section: Introductionmentioning
confidence: 99%